2006
DOI: 10.1097/01.olq.0000235169.45680.7c
|View full text |Cite
|
Sign up to set email alerts
|

A Cost-Effectiveness Evaluation of a Jail-Based Chlamydia Screening Program for Men and Its Impact on Their Partners in the Community

Abstract: Age-based screening could lower costs without substantially sacrificing effectiveness. Notifying partners of infected inmates was a cost-effective adjunct to screening inmates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 38 publications
0
15
0
Order By: Relevance
“…Although a handful of published cost-effectiveness analyses of correctional screening have shown the cost-effectiveness of screening in this venue, 6668 they were based on theoretical cohorts. In our review, programmatic cost data were lacking across the venues examined.…”
Section: Discussionmentioning
confidence: 99%
“…Although a handful of published cost-effectiveness analyses of correctional screening have shown the cost-effectiveness of screening in this venue, 6668 they were based on theoretical cohorts. In our review, programmatic cost data were lacking across the venues examined.…”
Section: Discussionmentioning
confidence: 99%
“…However, given the available data, this would not seem to be the case in many jurisdictions. In an earlier study, Gift et al [18] concluded that age-based chlamydia screening of male jail inmates (i.e. screening only men less than 30 years old) would identify almost as many cases as universal screening but at half the cost.…”
Section: Sexually Transmitted Disease Screening and Testingmentioning
confidence: 99%
“…Selectively testing only women at the highest risk for gonorrhea may diminish the risk of false-positive results and provide cost savings [17].…”
mentioning
confidence: 99%